Potential of Ulva linza L. and Caulerpa racemosa var. uvifera seaweeds from Cox’s Bazar, Bangladesh as sea vegetable - Aziz, A; Roy, SK; Hassan, A; Haque, MZ; Shahjadee, UF; Mondal, K; Mohanta, LC; Mashuk, OF; Saha, BK (Bangladesh Journal of Scientific and Industrial Research, 2021)
The nutritional quality parameters of leafy Ulva linza L. collected from the west coast of the Naf river estuary, Teknaf and grape-like Caulerpa racemosa var. uvifera collected from St. Martin's Island, Cox's Bazar, Bangladesh, were studied. Total protein content in U. linza (22.05±1.73%) was found significantly (p<0.05) higher than C. racemosa var. uvifera (18.20±1.50%) but with low crude lipids in the former; total amino acid content was also higher in the former, both having nearly the same amount of essential and non-essential amino acids; vitamin C content (about 2.5 mg/100 g) was nearly identical but β -carotene content was higher in the later (9.04 mg/100 g dry wt.). Crude fiber in U. linza was low (4.21±0.43%) but high in C. racemosa var. uvifera (18.20±1.50%). Other micronutrients were also ascertained. The nutritional quality parameters determined suggested that the “sea-salad” and “sea- grapes” can be used as sea-vegetables and food supplements. Bangladesh J. Sci. Ind. Res.56(3), 223-230, 2021